Crowdsourcing a short overview for the rest of us - Libert, Barry (FTPress Delivers elements, 2010)
This is the eBook version of the printed book. If the print book includes a CD-ROM, this content is not included within the eBook version. This is the eBook version of the printed book. If the print book includes a CD-ROM, this content is not included within the eBook version. Everything you need to know about crowdsourcing right now, to start using it for competitive advantage!The Web has connected nearly a billion people, amplifying all that individual brainpower with the power of technology. Suddenly, humans can act in mass collaboration, using the kind of collective intelligence once reserved for ants and bees--but with human IQ driving the mix. The result: a quantum increase in the world's ability to conceive, create, compute, and connect ... If you liked this Element, read more from Barry Libert and Jon Spector, including We Are Smarter Than Me: How to Unleash the Power of Crowds in Your Business (ISBN: 9780132244794). Available in print and digital formats.